PENGUATAN ORIENTASI KARIR BIDANG OTOMOTIF ANAK DIDIK LEMBAGA PEMBINAAN KHUSUS ANAK - Wulandari, Anastasia; Maslihah, Sri; Setiadi, Asep (Program Studi Psikologi Universitas Pendidikan Indonesia, 2020)
This service program is one of life skills education for LPKA students which is expected to be their provision for a career and build economic independence while living a free period and returning to the community (rer-entry). Life skills education provided in the form of vocational training in the field of automotive motorbikes with the aim to improve the career orientation of students of the Special Child Development Institute (LPKA). To test the effect of automotive training on the career orientation of LPKA students, an evaluation of the results of training for LPKA students using the design of one group pretest posttest to 29 LPKA students who will undergo a free period. The evaluation results show the career orientation of LPKA students can be developed through the provision of vocational training in the automotive field, namely the provision of knowledge and skills in pioneering motorcycle entrepreneurship. For future programs, especially related to the provision of vocational training, it is expected to increase the types of skills provided to facilitate the interests of different LPKA students.